Tanner-Whitehouse and modified Bayley-Pinneau adult height predictions in elite youth soccer players from the middle east - Lolli, L.; Johnson, A.; Monaco, M.; Cardinale, M.; Di Salvo, V.; Gregson, W. (Medicine & Science in Sports & Exercise, 2021)
Purpose: To provide the first scrutiny of adult height prediction protocols based on automated Greulich-Pyle and Tanner-Whitehouse (TW) skeletal ages applied to elite youth soccer players from the Middle East. Methods: We examined the application of modified Bayley-Pinneau (BoneXpert®), TW-II, and TW-III protocols using mixed-longitudinal data available for 103 subjects (chronological age range, 19.4 to 27.9 yr) previously enrolled as academy student-athletes (annual screening range, one to six visits). Random-effects generalized additive models quantified the presence of systematic mean differences between actual versus predicted adult height. Effects were deemed practically equivalent based on the location of the confidence interval (95% CI) against a realistic difference value of ? = ± 1 cm. Each model pooled residual standard deviation described the actual precision of height predictions and was used to calculate a 95% prediction interval. Results: The BoneXpert® method overpredicted adult height systematically at chronological ages in the range of approximately 13.5 to 14.5 yr (95% CI range, -1.9 to -1 cm) and Greulich-Pyle skeletal ages between 13.5 and 15 yr (95% CI range, -3.1 to -1 cm). Effects based on TW-II were practically equivalent across the chronological and skeletal age measurement ranges, with this protocol yielding adult height predictions with a precision (standard deviation) of approximately ±2.6 cm. The mean TW-III effects indicated systematic adult height overpredictions until the attainment of 14.5 and 15 yr of chronological age (95% CI range, -3.8 to -1.1 cm) and TW-III skeletal age (95% CI range: -5.2 to -2.3 cm), respectively. Conclusions: Tanner-Whitehouse-II adult height prediction method provided more consistent estimates and can be considered the method of choice for talent development purposes in youth soccer players from the Middle East.